STUDY OF THE MOTIVATIVE COMPONENT OF TECHNOLOGICAL COMPETENCE OF THE TEACHER OF PROFESSIONAL TRAINING - VAGANOVA, O.I; KOROSTELEV, A.A (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2021)
The growth in demand for blue-collar professions justified the need to improve the quality of personnel training. The state, focusing on the demand of society in the training of competitive specialists capable of carrying out professional activities in the new conditions, has subjected the system of professional education to significant changes. Institutions of secondary vocational education strive to meet the world educational standards of WorldSkills. First of all, the need for competent teachers of vocational training who owns educational technologies at a high level for the implementation of the training of workers, employees and mid-level specialists is actualized. In the formation of the technological competence of students of higher educational institutions, the motivational component is of particular importance. The article is aimed at analyzing the experience of the formation of the motivational component of the technological competence of vocational training bachelors. The technological competence of teachers of vocational training is a necessary element for the implementation of future professional activities and presupposes the bachelor's possession of innovative educational technologies, the ability to realize their capabilities in specific conditions. The study, aimed at studying the motivational component of technological competence, uses a methodology for diagnosing educational motivation of students. The results allow us to record the growth of professional and educational and cognitive motivation.